Senam Hamil Dalam Upaya Meningkatkan Kesehatan Dan Kesiapan Ibu Menghadapi Persalinan - St. Malka; Musni; Mutmainnah; Irawati (Pusat Riset dan Inovasi Nasional, 2023)
Pregnancy exercise is physical exercise in the form of certain movements that are carried out specifically to improve the health of pregnant women. Pregnancy exercise is a movement therapy therapy given to pregnant women to prepare themselves, both physically and mentally to face and prepare for fast, safe and spontaneous delivery. This community service activity is to improve the health of pregnant women and readiness for childbirth in pregnant women in the Bajoe Village. The method used is direct counseling to pregnant women and the practice of pregnancy exercise. The results of this activity are expected that pregnant women understand the benefits of pregnancy exercise and are willing to carry it out routinely at home so that their health during pregnancy is maintained and ready for delivery so that delivery goes smoothly, mother and baby are healthy.